2017
DOI: 10.1002/acs.2762
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation of coronary tree in CT angiography images

Abstract: The International Journal of Adaptive Control and Signal Processing is concerned with the design, synthesis and application of estimators or controllers where adaptive features are needed to cope with uncertainties. Papers on signal processing should also have some relevance to adaptive systems. The journal focus is on model based control design approaches rather than heuristic or rule based control design methods. All papers will be expected to include significant novel material. Both the theory and applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…[ 12 18 ] Meanwhile, as time goes on, more and more image processing technologies come into view. [ 19 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 18 ] Meanwhile, as time goes on, more and more image processing technologies come into view. [ 19 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al developed an automatic approach to segment the three-dimensional coronary tree from CTA images. [31] Further study is needed to investigate the 3D CTA for the visualization of CCC with automatic segmentation of coronary tree.…”
Section: Discussionmentioning
confidence: 99%
“…Prompt and accurate diagnosis of compromised myocardial perfusion is crucial and has been the focus of upcoming research to improve the performance of diagnostic imaging. [ 14 , 15 ] As mentioned earlier, symptoms of CAD and pulmonary hypertension often overlap, making the clinical differentiation of these entities challenging. Left undiagnosed and untreated, pulmonary hypertension may have a debilitating effect on the lives of patients; studies have shown that the symptoms of pulmonary hypertension can adversely affect the physical, emotional, and social factors governing patient health-related quality of life.…”
Section: Discussionmentioning
confidence: 99%